Design validation of the working surface of a sheep’s foot roller for compaction of freshly prepared soil - Artemenko, D.; Nastoyaschiy, V.; Darienko, V.; Артеменко, Д. Ю.; Настоящий, В. А.; Дарієнко, В. В. (Magnolithe GmbH, 2018)
It is determined that the main factors which influence the process of soil compaction are the design of the roller working element and physical and mechanical characteristics of the soil. The process of interaction between the roller and the soil was studied with the help of math modelling. It was defined that the character of the contact pressure distribution under the roller surface corresponds to its design characteristics. A modified design of the roller drum and foot was introduced.
Keywords: roller drum; compaction of the soil; a foot of the roller; the working surface of the roller; ролик барабана; ущільнення грунту; валець ґрунтового кулачкового котка; кулачок ґрунтового котка